LB-13. Economic and workload impact of COVID-19 pandemic on physicians in the United States: results of a national survey. (31st December 2020) - Long, Dustin; Long, Dustin; Turner, Wesli; Chapman Lambert, Crystal; Creger, Thomas; Mugavero, Michael J; Burkholder, Greer A
Abstract: Background: The United States (US) healthcare system has experienced enormous economic impact due to the COVID-19 pandemic, driven by both loss of revenue related to shutdowns and increased strain on resources. These factors have impacted the workload and finances of physicians. Methods: A 31-item anonymous survey evaluating the psychological impact of the COVID-19 pandemic on physicians was developed at the University of Alabama at Birmingham using Qualtrics XM software and included questions on adverse economic impact (defined as selecting job loss, furlough or reduced income as a stressor), workload, and compensation. It was distributed via physician professional and social networks including email, Facebook groups, and #MedicalTwitter May 14-July 31, 2020. Results: Among 597 respondents, 295 (49%) reported adverse economic impact, with the highest proportions among emergency medicine (71%), anesthesiologists (63%), and surgeons (60%) and lowest among infectious diseases (ID) (25%). In multivariable analysis (Table), physicians practicing in the Northeastern US saw the lowest economic impact versus the South (OR 3.44, 95% CI: 2.03–5.84), Midwest (2.62, 1.36–5.05) or West (1.98, 1.06–3.71). Physicians practicing in federal or academic settings experienced less economic impact than those in community settings (0.09, 0.03–0.30 and 0.61, 0.41–0.93 respectively). Increased work hours were identified by 185 (31%) of respondents as a stressor, with 169 (92%) reporting additional hours were partially or completely uncompensated. Among 584 respondents, 212 (36%) had new roles and responsibilities (Figure), with the highest proportion among ID physicians (75%). Table 1: Characteristics and factors associated with reporting adverse economic impact of the COVID-19 pandemic among 597 physicians in the United States Figure: New roles and responsbilities assumed by 212 physicians during the COVID-19 pandemic Conclusion: The COVID-19 pandemic has increased physician workload, with approximately one-third of physicians taking on new responsibilities and a similar proportion reporting increased work hours. Much of this additional work is uncompensated due to the economic impact of the pandemic on the healthcare system. Simultaneously, many physicians across the US have suffered adverse economic consequences, especially in the South. ID physicians have experienced higher workload but less economic impact, related to increased need for their expertise and new roles and responsibilities. Disclosures: Dustin Long, PhD, Nothing to disclose